Imprinting of the Y Chromosome Influences Dosage Compensation in roX1 roX2 Drosophila melanogaster - Menon, Debashish U; Meller, Victoria H (Genetics (Austin), 2009)
Drosophila melanogaster males have a well-characterized regulatory system that increases X-linked gene expression. This essential process restores the balance between X-linked and autosomal gene products in males. A complex composed of the male-specific lethal (MSL) proteins and RNA is recruited to the body of transcribed X-linked genes where it modifies chromatin to increase expression. The RNA components of this complex, roX1 and roX2 (RNA on the X1, RNA on the X2), are functionally redundant. Males mutated for both roX genes have dramatically reduced survival. We show that reversal of sex chromosome inheritance suppresses lethality in roX1 roX2 males. Genetic tests indicate that the effect on male survival depends upon the presence and source of the Y chromosome, revealing a germ line imprint that influences dosage compensation. Conventional paternal transmission of the Y chromosome enhances roX1 roX2 lethality, while maternal transmission of the Y chromosome suppresses lethality. roX1 roX2 males with both maternal and paternal Y chromosomes have very low survival, indicating dominance of the paternal imprint. In an otherwise wild-type male, the Y chromosome does not appreciably affect dosage compensation. The influence of the Y chromosome, clearly apparent in roX1 roX2 mutants, thus requires a sensitized genetic background. We believe that the Y chromosome is likely to act through modulation of a process that is defective in roX1 roX2 mutants: X chromosome recognition or chromatin modification by the MSL complex.